Grand challenges in environmental sciences (National Academy Press, 2001)
Scientists have long sought to unravel the fundamental mysteries of the land, life, water, and air that surround us. To identify high-priority environmental science projects, this work explores the important areas of research. It aims to determine areas of opportunity that - with a concerted investment - could yield significant findings.